The cause of deactivation of VOx/TiO2 catalyst by thermal effect and the role of tungsten addition. (16th January 2021) - Won, Jong Min; Kim, Min Su; Hong, Sung Chang
Graphical abstract: Highlights: Deactivation factors are oxidation of NH3 and formation of TiVO solid solution. The formation of a terminal polymeric VO species positively influenced the low-temperature SCR activity. Crystalline WO species are mainly formed on TiO2 surface, and Polymeric W is mainly formed inside TiO2 . Abstract: We investigated the changes of catalytic activities, characteristics, and cause of deactivation of the V/Ti and V/W/Ti-based various catalysts mainly used in NH3 -SCR according to the thermal effects and roles of W addition. The physical and chemical properties of the catalysts were analyzed by XRD, XPS, SEM/EDX, Raman, TPD, DRIFT analyses. The main causes of deactivation of SCR activity include a formation of crystalline V at high temperature, and the solid solution phenomenon forming the TiVO structure at low temperature. Moreover, an enhancement of the low temperature activity due to the formation of terminal polymeric VO species was concurrently observed with the formation of V2 O5 . When W was loaded on the VOx/TiO2 catalysts, the crystalline WO structure partially inhibited the formation of crystalline V2 O5, while polymeric W inhibited the reduction of the specific surface area and formation of the TiVO solid solution.